In silico molecular analysis of fructooligosaccaride producing enzymes - Nurul Wahida, Abdullah; Shariza, Jamek (2021)
Putative glycosyl hydrolase (GH) 68 fructosyltransferase (FTase) from Streptococcus thermophilus (VUW839976.1) was identified as potential fructooligosaccharides (FOS) producing enzyme. Computational study using in silico molecular analysis was used as alternative approach to discover this potential enzyme.